1998
DOI: 10.1143/jjap.37.1325
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication Technology of Ferroelectric Memories

Abstract: We study the effect of magnetic field on charge transport in a metal/G4-DNA/metal device based on the lattice Green function method and Landauer-Büttiker theory. The basic transport property of the device is closely related to the coupling method between the G4-DNA molecule and metal electrodes. A magnetoresistance (MR) as large as 16% is obtained with a magnetic field on the order of 1 T. The special helix structure of the G4-DNA molecule will have a dramatic effect on the magnetic response of the device. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…[1][2][3] Crystallinity and surface morphology of bottom electrodes have been reported to influence the electrical properties of capacitors, such as dielectric constant, leakage current and polarization-electric field (P-E) hysteresis behavior. [3][4][5] Although there have been reports [6][7][8] on epitaxial growth of SrTiO 3 and Pb(Zr,Ti)O 3 (PZT) films on single-crystal Si and MgO substrates, single-axis-oriented growth of dielectric layers on highly textured electrode films deposited on Si and SiO 2 /Si substrates 3,9) seems to be a more practical technique for applications to DRAM and FeRAM technology.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Crystallinity and surface morphology of bottom electrodes have been reported to influence the electrical properties of capacitors, such as dielectric constant, leakage current and polarization-electric field (P-E) hysteresis behavior. [3][4][5] Although there have been reports [6][7][8] on epitaxial growth of SrTiO 3 and Pb(Zr,Ti)O 3 (PZT) films on single-crystal Si and MgO substrates, single-axis-oriented growth of dielectric layers on highly textured electrode films deposited on Si and SiO 2 /Si substrates 3,9) seems to be a more practical technique for applications to DRAM and FeRAM technology.…”
Section: Introductionmentioning
confidence: 99%
“…This fatigue behavior was caused by function of oxide electrodes as a sink for oxygen vacancies 5,10) . In previous study, it is clearly revealed that oxide electrodes can improve the film fatigue resistance 11,12) When the cycling voltage was 10 V, PLZT capacitors with Pt top electrodes showed significant degradation of polarization after 10 4 cycles. PLZT capacitors with AZO and ITO top electrodes should be robust electrodes compared with Pt top electrodes after 10 5 cycles.…”
Section: Methodsmentioning
confidence: 94%
“…Thin films of platinum-group metal, such as Pt, Ru, and Ir, have attracted much attention as bottom-electrode material for storage capacitors used in dynamic random-access memories (DRAMs) and nonvolatile ferroelectric randomaccess memories (FeRAMs). 1,2) The film crystallinity and surface morphology of bottom electrodes have been reported to influence electrical properties such as the dielectric constant, leakage current, and polarization-electric field (P-E) hysteresis behavior.…”
Section: Introductionmentioning
confidence: 99%